Colores. - Dorling Kindersley (Buenos Aires : Sigmar, 1992)
Photographs explore the concept of color, from red cherries and yellow duck to blue marbles and other colorful objects.
Translation of: My first look at-- colours.
"Un libro Dorling Kindersley"--T.p. verso.
Keywords: Colors -- Juvenile literature; Spanish language materials -- Juvenile literature; Picture books